Correlation between Invasive Intracranial Pressure Monitoring and Optic Nerve Sheath Diameter in Patients with Traumatic Brain Injury - Shrestha, B.; Shrestha, P.; Ghale, P.; Lakshmipathy, G. (Kathmandu University Medical Journal, 2021)
Background In management of patients with traumatic brain injury, intracranial pressure holds an important place. Any untoward rise in intracranial pressure portends dreaded complications. Hence, any delay in detecting the issue is considered unacceptable. Objective This study focuses on analyzing the correlation between ultrasound derived optic nerve sheath diameter and intracranial pressure values derived from invasive intracranial pressure monitoring system in a neurosurgical patient with severe traumatic brain injury. Method A prospective observational study was performed using a convenience sample technique including all adult patients with traumatic brain injury who had invasive intracranial monitors placed as part of their clinical care. Ocular ultrasound was performed with 5 - 7.5 MHz linear probe of ACUSON X300 ultrasound system while simultaneous intracranial pressure readings were obtained directly from an invasive intracranial pressure monitoring system. The association between optic nerve sheath diameter and invasive intracranial pressure reading was assessed with the Pearson’s correlation coefficient and a receiver operator characteristic curve was created to determine the optimal optic nerve sheath diameter cutoff to detect intracranial pressure > 15 cm H2O. Result One hundred and fifteen ocular ultrasounds were performed on 30 individual patients. The mean age of the population involved in this study is 42.13 years ± 1.89 with male preponderance in the ratio of 6:1. Pearson’s correlation coefficient of optic nerve sheath diameter and intracranial pressure was found to be 0.844 (p < 0.000) demonstrating a significant positive correlation. The area under the receiver operating characteristic curve was found to be 0.961 (95% confidence interval = 0.93 to 0.99). Based on analysis of the receiver operating characteristic curve, optic nerve sheath diameter > 4.85 mm performed best to detect intracranial pressure > 15 cm H2O with a sensitivity of 93.5% and specificity of 83%. Conclusion Optic nerve sheath diameter is a dependable screening tool to evaluate for elevated intracranial pressure among patients with traumatic nerve injury.